2014
DOI: 10.1186/1476-511x-13-149
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Apolipoprotein AI, B gene polymorphism and the risk of non-traumatic osteonecrosis

Abstract: BackgroundPrevious studies suggested that Apolipoprotein AI (ApoAI) and apolipoprotein B (ApoB) gene polymorphisms may result in lipid metabolism disorders. Genetic polymorphisms in these genes may be associated with the occurrence of osteonecrosis.MethodsWe designed a case-control study including 429 patients of osteonecrosis and 368 age- and sex-matched control subjects. Polymerase chain reaction was used to amplify the DNA fragments in promoter -75 G > A of ApoAI gene and EcoR I, Xba I and 3′-VNTR of ApoB g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…[ 2 , 3 ] In China, with its massive population, 150,000 to 200,000 new cases of ONFH are diagnosed every year. [ 4 ] Because a significant number of patients with ONFH are young (20–40 years old), and the long-term survivorship of prosthesis is uncertain, preserving their own joints is preferable. Encouraging results of hip joint preservation at short-term and midterm follow-up have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 3 ] In China, with its massive population, 150,000 to 200,000 new cases of ONFH are diagnosed every year. [ 4 ] Because a significant number of patients with ONFH are young (20–40 years old), and the long-term survivorship of prosthesis is uncertain, preserving their own joints is preferable. Encouraging results of hip joint preservation at short-term and midterm follow-up have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies found that SNPs in several genes might be associated with patients’ susceptibility to orthopedic diseases, [25,26] including alcohol-induced ONFH. [27] Investigation of the relationship between different genes and diseases can improve the treatment, prevention, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological study of osteonecrosis in China showed that steroid-induced and alcoholic-induced ONFH accounted for 54.8% [4]. The prompt onset of non-traumatic ONFH is not easy to detect, and the progress is rapid, so a large number of late patients can only accept hip replacement surgery [5,6]. Therefore, the study of the etiology and pathogenesis of ONFH can provide the basis for timely diagnosis.…”
Section: Introductionmentioning
confidence: 99%